2009
DOI: 10.1097/aln.0b013e318190b4d9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Use of Statins Is Associated with Reduced Early Delirium Rates after Cardiac Surgery

Abstract: Preoperative administration of statins is associated with the reduced risk of postoperative delirium after cardiac surgery with cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
159
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(169 citation statements)
references
References 53 publications
(39 reference statements)
4
159
1
5
Order By: Relevance
“…20 The current study confirms these findings, extending the beneficial role of statin therapy to the vascular surgical population. Conversely, a retrospective administrative cohort analysis in older patients undergoing elective surgery found statins to increase delirium.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…20 The current study confirms these findings, extending the beneficial role of statin therapy to the vascular surgical population. Conversely, a retrospective administrative cohort analysis in older patients undergoing elective surgery found statins to increase delirium.…”
Section: Discussionsupporting
confidence: 84%
“…44 Our study re-confirms a number of previous reports that identify aortic reconstruction, preoperative depression, and cerebrovascular disease as risk factors for postoperative delirium. 4,20,45,46 Complex vascular procedures and significant atherosclerosis reflected as severe peripheral or cerebrovascular disease may predispose patients to multiorgan dysfunction and delirium. Patients with vascular disease have lower reserve to cope with blood loss, hemodynamic instability, and inflammatory response associated with major vascular surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…164 Nevertheless, because there are other important reasons for the elderly to take statins, we can expect to need to anesthetize many AD patients who are on statins. If the evidence from stroke 165 and CABG 166 patients applies, statin therapy should not be withdrawn without specific indication for withdrawal.…”
Section: Potential Alleviating Factorsmentioning
confidence: 99%
“…[20] However, a small observational study failed to show any cognitive-sparing effect of statins nor any reduction in neuroinflammatory biomarkers. [21] Additional observational studies are conflicting regarding an association between statins and postoperative delirium, with one study reporting a 46% reduction in postoperative delirium after cardiac surgery [20] while a large observational study of patients undergoing a mix of cardiac and noncardiac surgery found preoperative statin therapy associated with an increased risk for postoperative delirium. Systematic reviews in the nonsurgical setting do not support a significant effect of statins on cognitive function.…”
Section: Other Outcomesmentioning
confidence: 99%